2014
DOI: 10.1038/cdd.2014.92
|View full text |Cite
|
Sign up to set email alerts
|

Fbxo45-mediated degradation of the tumor-suppressor Par-4 regulates cancer cell survival

Abstract: Prostate apoptosis response protein 4 (Par-4) also known as PRKC apoptosis WT1 regulator is a tumor suppressor that selectively induces apoptosis in cancer cells. However, its post-translational regulation by ubiquitin-mediated proteolysis and the cellular machinery that is responsible for its proteasomal degradation are unknown. Using immunopurification and an unbiased mass spectrometry-based approach, we show that Par-4 interacts with the SPRY-domain containing E3 ubiquitin ligase Fbxo45 through a short cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 32 publications
(55 reference statements)
0
58
0
Order By: Relevance
“…In mature neurons, PHR proteins take on an important role in axon degeneration following injury (27,28). Outside of the nervous system, PHR proteins are implicated in oncogenesis (29)(30)(31)(32)(33)(34). Despite growing recognition of the functional importance of PHR proteins, relatively little is known about how components of atypical PHR ubiquitin ligase complexes assemble.…”
mentioning
confidence: 99%
“…In mature neurons, PHR proteins take on an important role in axon degeneration following injury (27,28). Outside of the nervous system, PHR proteins are implicated in oncogenesis (29)(30)(31)(32)(33)(34). Despite growing recognition of the functional importance of PHR proteins, relatively little is known about how components of atypical PHR ubiquitin ligase complexes assemble.…”
mentioning
confidence: 99%
“…To address this critical question, this group detected the sensitivity of cancer cells expressing the Par-4 wild-type (WT) or Par-4 (3A) mutant to staurosporine-induced apoptosis. 15 To this end, they reported that cells expressing Par-4 (3A) mutant have a significant increase in the number of apoptotic cells compared to the cells with Par-4 (WT). 15 Consistently, TUNEL and western blot analyses for cleaved PARP-1 as additional apoptotic markers confirmed that Par-4 (3A) mutant promoted staurosporineinduced apoptosis.…”
mentioning
confidence: 99%
“…15 To this end, they reported that cells expressing Par-4 (3A) mutant have a significant increase in the number of apoptotic cells compared to the cells with Par-4 (WT). 15 Consistently, TUNEL and western blot analyses for cleaved PARP-1 as additional apoptotic markers confirmed that Par-4 (3A) mutant promoted staurosporineinduced apoptosis. In support of this conclusion, they further showed that misregulated degradation of Par-4 by depletion of Fbxo45 or mutating the degron could also trigger cellular apoptosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations